Patterns of opioid utilization in the 90-days post hospital discharge and risk of re-admissions and emergency department visits. (2018) - Kurteva, Siyana; Weir, Daniala; Schmidt, Alexandra; Lee, Todd; Tamblyn, Robyn
No abstract available